Transient images : personal media in public frameworks - Freedman, Eric, 1965- (Temple University Press, 2011)
In this probing study, Eric Freedman focuses on what images from photography, mobile communications, and the Internet reveal about looking. Exploring subjectivity by critically examining the look, he elaborates on the nature of the photographic frame and its relation to interpretive practices. Freedman scrutinizes what he calls "technobiography"a life written through technology, and considers the movement of personal images into public spaces. He also considers authorship that situates the self as inherently engaged with and inscribed by information technology. All of the chapt.